Fully crystalline MWW structure titanium silicon molecular sieve catalyst and its preparation method and application
By adding specific additives and performing solution treatment in the molding and processing of the MWW structure titanium silicon molecular sieve catalyst, the problems of poor titanium species, small micropore volume, low mechanical strength and poor catalytic performance of the catalyst are solved, and an efficient olefin epoxidation reaction is achieved.
Patent Information
- Application Number
- CN202111182501.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-11
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-10-11
AI Technical Summary
The existing MWW structure titanium silicon molecular sieve catalysts have problems such as poor titanium species state, small micropore volume, low mechanical strength and poor catalytic performance.
The fully crystallized MWW structure titanium silicon molecular sieve catalyst is used, and fluoride, amorphous binder and pore-forming agent are added during the molecular sieve molding process, and crystallized in the environment of organic amine solution, and then solution treatment is carried out to improve the titanium species state and micropore structure.
It has achieved a fully crystalline MWW structure titanium silicon molecular sieve catalyst with good titanium species, large micropore volume, high mechanical strength and excellent catalytic performance, and is suitable for olefin epoxidation reaction.
Smart Images

Figure CN115957808B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a fully crystalline MWW structure titanium silicon molecular sieve catalyst and a preparation method and application thereof, belonging to the field of molecular sieve catalysts. Background Art
[0002] Epoxides are important organic chemical intermediates, mainly including ethylene oxide, propylene oxide, 1,2-epoxypentane and 1,2-epoxyhexane. At present, epoxy compounds are basically produced by selective oxidation with olefins as raw materials. For example, ethylene oxide is obtained by epoxidation of ethylene and air under the action of silver catalyst; the industrial production routes of propylene oxide mainly include chlorohydrin method and co-oxidation method. The former is gradually replaced by other processes due to serious pollution, while the latter has a long process flow and large construction investment. The co-products produced are almost 2 to 4 times the output of propylene oxide. The market demand for co-products has a great impact on the process; the industrial production method of 1,2-epoxypentane and 1,2-epoxyhexane is 1-pentene and 1-hexene peroxyformic acid oxidation method, which has problems such as severe equipment corrosion and poor atom economy.
[0003] In the eighties of last century, EniChem company proposed a novel method for producing propylene oxide, i.e. hydrogen peroxide oxidation method (HPPO) (US4410501), which adopts the TS-1 molecular sieve of MFI structure as catalyst, makes propylene and hydrogen peroxide react in solvent methanol to generate propylene oxide, and this process has the characteristics of environmental protection and high raw material utilization, and has realized industrialization at present. In 2007, Wu Peng et al. found that the titanium silicon molecular sieve with MWW structure showed better catalytic activity in olefin epoxidation process, and eliminated the alcohol ether by-product in TS-1 system, and the selectivity of epoxide was obviously improved (Studies in Surface Science and Catalysis, 2007, 170, 1236). In addition, the synthesis cost of MWW structure titanium silicon molecular sieve is lower than TS-1 molecular sieve, so the high performance olefin epoxidation process based on MWW structure titanium silicon molecular sieve is of great significance.
[0004] At present, the industrial production of propylene oxide is mainly carried out in a fixed bed reactor, and the micron or nanometer-sized titanium silicon molecular sieve powder obtained by hydrothermal method has low strength itself, and is easily entrained by the reaction liquid during the reaction, causing the device pipeline to be blocked. In addition, after the reaction is completed, it is difficult to separate and recover the catalyst powder from the reaction liquid, and it is impossible to achieve efficient and continuous production in a fixed bed reactor. CN1346705A proposes to use small balls with certain mechanical strength as carriers, and to enrich the titanium silicon molecular sieve on its surface by rolling ball molding to improve the mechanical strength of the catalyst. CN1268400A proposes to use aluminum oxide as a carrier to prepare a titanium silicon molecular sieve catalyst that meets the requirements of industrial application. CN103464197B proposes to mix TS-1 with oxides and then perform alkali treatment to improve the mechanical strength of the catalyst.
[0005] For the molded titanium silicon molecular sieve catalyst, although the addition of inert binder can improve the mechanical strength of the catalyst, it will also cause the overall active component ratio of the catalyst to decrease, part of the pores are blocked, the micropore volume decreases, resulting in substrate diffusion being restricted, the activity of the catalyst is reduced, and it is easier to carbonize and deactivate. In order to eliminate the negative impact of the binder, CN112354557A discloses a monolithic titanium zeolite catalyst preparation method and its application, by mixing an amorphous silicon-based binder and a polymer pore-forming agent into MWW titanium zeolite powder, adding water to stir and knead, mechanically forming and roasting, and then immersing in a composite annular nitrogen-containing organic aqueous solution to seal and heat, after filtering, drying, and roasting, a monolithic propylene continuous epoxidation catalyst is obtained. Although there is no binder, the catalytic performance of the catalyst is still relatively low, and the mechanical strength is less than 30N / cm, which is difficult to meet the requirements of industrial applications. On the other hand, the composite annular nitrogen-containing organic used in the preparation is complex and expensive, making the preparation cost of the catalyst extremely high, and it is impossible to carry out large-scale industrial production.
[0006] In general, the MWW structured titanium silicon molecular sieve catalysts in the prior art, regardless of whether they contain a binder, have the problems of low mechanical strength and poor catalytic performance. It is necessary to develop MWW structured titanium silicon molecular sieve catalysts with large micropore volume, high mechanical strength and good catalytic performance. Summary of the invention
[0007] One of the technical problems to be solved by the present invention is to solve the problems of poor titanium species state, small micropore volume, low mechanical strength and poor catalytic performance of the existing MWW structure titanium silicon molecular sieve catalyst, and to provide a fully crystalline MWW structure titanium silicon molecular sieve catalyst. The catalyst has the characteristics of good titanium species state, large micropore volume, high mechanical strength and excellent catalytic performance.
[0008] The second technical problem to be solved by the present invention is to solve the problem that there is currently no method for preparing MWW structured titanium silicon molecular sieve catalysts with good titanium species state, large micropore volume, high mechanical strength and excellent catalytic performance, and to provide a method for preparing fully crystalline MWW structured titanium silicon molecular sieve catalysts.
[0009] The third technical problem to be solved by the present invention is to provide an application of a fully crystalline MWW structured titanium silicon molecular sieve catalyst in olefin epoxidation reaction.
[0010] In order to solve one of the above technical problems, the present invention provides a fully crystalline MWW structure titanium silicon molecular sieve catalyst in the first aspect, wherein the ultraviolet Raman spectrum of the molecular sieve catalyst is 343±6cm -1 、485±6cm -1 、529±6cm -1 and 1094±6cm -1 A peak appears at the spectral point.
[0011] According to the present invention, further, in the molecular sieve catalyst, the molar ratio of silicon to titanium (n Si / n Ti ) is 5 to 500, preferably 10 to 200.
[0012] According to the present invention, further, the molecular sieve catalyst includes at least one element selected from boron and aluminum, preferably boron. In the molecular sieve catalyst, the molar ratio of boron to silicon (n B / n Si ) is 0 to 0.10, preferably 0 to 0.040, more preferably 0.001 to 0.040; in terms of atoms, the aluminum-silicon molar ratio (n Al / n Si ) is 0 to 0.10, preferably 0 to 0.04.
[0013] According to the present invention, further, the micropore volume of the molecular sieve catalyst is 0.10 to 0.20 cm 3 / g, preferably 0.12 to 0.18 cm 3 / g.
[0014] According to the present invention, further, the mechanical strength of the molecular sieve catalyst is 30 to 100 N / cm, preferably 40 to 90 N / cm.
[0015] In order to solve the second technical problem mentioned above, the second aspect of the present invention provides a method for preparing a fully crystalline MWW structured titanium silicon molecular sieve catalyst, comprising the following steps:
[0016] (1) kneading MWW structure titanium silicon molecular sieve powder, a binder, a pore-forming agent, and a fluoride into a mold, and first calcining to obtain a molded product;
[0017] (2) crystallizing the product obtained in step (1) in an environment containing an organic amine solution to obtain a catalyst precursor;
[0018] (3) treating the catalyst precursor of step (2) with solution A, performing a second calcination, and then treating with solution B to obtain the molecular sieve catalyst.
[0019] According to the present invention, further, the MWW structure titanium silicon molecular sieve powder in step (1) has a silicon-titanium molar ratio of 5 to 500 in terms of atoms.
[0020] According to the present invention, further, the binder in step (1) is an amorphous binder, comprising a silicon source and at least one selected from a boron source and an aluminum source; preferably, the amorphous binder comprises a silicon source and a boron source. In the composition of the binder, in terms of oxides, the molar ratio SiO2:B2O3:Al2O3=1:x:y, wherein x=0~1, y=0~1, x+y=0.01~2. The binder is prepared by uniformly mixing the raw materials of each component.
[0021] According to the present invention, further, in the binder composition, the silicon source is selected from at least one of silica sol, water glass, silicon powder and tetraethyl orthosilicate; the boron source is selected from at least one of boric acid, boron trioxide and borates; the aluminum source is selected from at least one of aluminum trioxide, aluminum hydroxide, sodium aluminate, aluminum nitrate and aluminum sulfate.
[0022] According to the present invention, further, the pore-forming agent in step (1) is selected from at least one of sesbania powder, cellulose, chitosan, lignin, starch, polyethylene glycol, triblock copolymers P123 and F127.
[0023] According to the present invention, further, the fluoride in step (1) is selected from at least one of sodium fluoride, potassium fluoride and ammonium fluoride.
[0024] According to the present invention, further, the mass ratio of the raw materials in step (1), MWW structure titanium silicon molecular sieve powder, binder, pore former and fluoride is 1:0.1-1.5:0.005-0.1:0.01-0.5.
[0025] According to the present invention, further, in the process of kneading and molding in step (1), an appropriate amount of water can be added according to molding needs. After kneading and molding, drying is performed. The drying conditions are 60-120° C. and drying for 1-24 hours.
[0026] According to the present invention, further, in step (1), the first calcination condition is calcination at 450-650° C. in an oxygen-containing atmosphere for 4-12 hours.
[0027] According to the present invention, further, the specific process of crystallization in the environment containing organic amine solution in step (2) is as follows: in step (1), the molded object is placed above the organic amine solution for crystallization, and the molded object is not in contact with the organic amine solution. The organic amine is at least one selected from piperidine and hexamethyleneimine. The concentration of the organic amine solution is 0.2 to 20 mol / L. The mass ratio of the molded object to the organic amine solution is 0.1 to 10:1. The conditions for the crystallization are: crystallization in a closed environment under autogenous pressure, the crystallization temperature is 130 to 190°C, and the crystallization time is 1 to 9 days. The product after crystallization is washed and dried, and the drying conditions are drying at 60 to 120°C for 1 to 24 hours. The synthesis of the catalyst precursor in step (2) does not include calcination.
[0028] According to the present invention, further, the treatment with solution A and the treatment with solution B in step (3) can be carried out by immersion.
[0029] According to the present invention, further, the solute A in the A solution is at least one selected from nitric acid, hydrogen chloride, sulfuric acid, formic acid, acetic acid and oxalic acid. The concentration of the A solution is 0.2 to 12 mol / L. The solid-liquid mass ratio of the catalyst precursor to the A solution in the A solution treatment is 1:10 to 80. The temperature of the A solution treatment is 60 to 130°C, and the time is 1 to 48 hours.
[0030] According to the present invention, further, the solute B in the B solution is at least one selected from nitric acid, hydrogen chloride, sulfuric acid, formic acid, acetic acid, oxalic acid, ammonium nitrate, ammonium chloride, ammonium sulfate, potassium nitrate, potassium chloride, sodium chloride and sodium sulfate. The concentration of the B solution is 0.0001-0.1 mol / L. The solid-liquid mass ratio of the catalyst precursor to the B solution in the B solution treatment is 1:10-80. The temperature of the B solution treatment is 20-100°C and the time is 1-48 hours.
[0031] According to the present invention, further, the product after treatment with solution A in step (3) is washed and dried, and the drying is performed at 60 to 120° C. for 1 to 24 hours.
[0032] According to the present invention, further, in step (3), the second calcination condition is calcination at 450-650° C. in an oxygen-containing atmosphere for 4-12 hours.
[0033] According to the present invention, further, the product after the treatment with the solution B in step (3) is washed, dried and optionally calcined to obtain the molecular sieve catalyst. Wherein, optional calcination means that calcination may be performed after drying or not. The drying is performed at 60 to 120° C. for 1 to 24 hours. The calcination conditions are calcination at 450 to 650° C. in an oxygen-containing atmosphere for 4 to 12 hours.
[0034] According to the present invention, further, the molecular sieve catalyst in step (3) includes at least one element of boron and aluminum. In terms of atoms, the molar ratio of silicon to titanium is 5 to 500, preferably 10 to 200; in terms of atoms, the molar ratio of boron to silicon is 0 to 0.10, preferably 0 to 0.040, more preferably 0.001 to 0.040; in terms of atoms, the molar ratio of aluminum to silicon is 0 to 0.10, preferably 0 to 0.04.
[0035] The present invention also provides a fully crystalline MWW structured titanium silicon molecular sieve catalyst prepared by the method.
[0036] According to the present invention, further, in the ultraviolet Raman spectrum of the molecular sieve catalyst prepared by the method, at 343±6cm -1 、485±6cm -1 、529±6cm -1 and 1094±6cm -1 A peak appears at the spectral point.
[0037] According to the present invention, further, in the molecular sieve catalyst prepared by the method, the micropore volume is 0.10 to 0.20 cm 3 / g, preferably 0.12 to 0.18 cm 3 / g.
[0038] According to the present invention, further, in the molecular sieve catalyst prepared by the method, the mechanical strength is 30 to 100 N / cm, preferably 40 to 90 N / cm.
[0039] In order to solve the third of the above technical problems, the present invention provides an application of the above fully crystalline MWW structured titanium silicon molecular sieve catalyst in olefin epoxidation reaction.
[0040] According to the present invention, further, the applying step comprises: mixing olefin, aqueous hydrogen peroxide solution, solvent and at least one alkaline substance as a raw material liquid, and contacting and reacting with the catalyst. The reaction device is a fixed bed reactor.
[0041] According to the present invention, further, the olefin is a liquefied olefin; the olefin includes at least one selected from propylene, butene, pentene, cyclopentene, hexene and cyclohexene; the mass fraction of hydrogen peroxide in the aqueous hydrogen peroxide solution is 10% to 70%; the solvent is at least one selected from methanol, acetonitrile, propionitrile, acetone and tert-butanol; the alkaline substance is at least one selected from ammonia water, potassium hydroxide, sodium hydroxide, ammonium carbonate, potassium carbonate, sodium carbonate, ammonium dihydrogen phosphate, potassium dihydrogen phosphate and sodium dihydrogen phosphate.
[0042] According to the present invention, further, in the raw material liquid, the molar ratio of olefin to hydrogen peroxide is 1:0.3-1; the mass fraction of olefin in the raw material liquid is 1%-50%; the mass fraction of solvent in the raw material liquid is 30%-90%; the mass concentration of the alkaline substance in the raw material liquid is 1-50ppm.
[0043] According to the present invention, further, the flow rate of the catalyst per unit mass of the raw material liquid is 3 to 30 mL·g cat. -1 ·h -1 ; The reaction temperature is 30-100°C, and the reaction pressure is 0.1-4MPa.
[0044] Compared with the prior art, the present invention has the following advantages:
[0045] 1. In the present invention, the ultraviolet Raman spectrum of the fully crystalline MWW structure titanium silicon molecular sieve catalyst is 343±6cm -1 、485±6cm -1 、529±6cm -1 、1094±6cm -1 Spectral peaks appear at , which are all attributed to the framework tetracoordinated titanium species, indicating that the titanium species is in good condition, and the molecular sieve catalyst does not contain an amorphous binder, has a large micropore volume, and has high mechanical strength. The molecular sieve catalyst is used in olefin epoxidation reactions and has the characteristics of high catalytic activity, high selectivity, and good stability.
[0046] 2. In the present invention, the preparation method of the catalyst is firstly to add fluoride, amorphous binder, and pore former in the molecular sieve forming process, preferably the amorphous binder includes silicon source and boron source, then crystallize in an organic amine solution environment to obtain a catalyst precursor, and finally the catalyst precursor is subjected to solution treatment to obtain the catalyst. The preparation method of the present invention can efficiently convert the binder into a molecular sieve, increase the micropore volume, improve the mechanical strength, and obtain a fully crystalline molecular sieve catalyst precursor. The preparation method improves the titanium species state of the molecular sieve through two solution treatments to obtain a fully crystalline MWW structure titanium silicon molecular sieve catalyst containing a skeleton tetracoordinated titanium species in a good state, a large micropore volume, and high mechanical strength. The catalyst prepared by the method of the present invention is used in olefin epoxidation reaction, and has excellent catalytic activity, selectivity, and stability.
[0047] 3. The catalyst of the present invention is used in olefin epoxidation reaction, has excellent catalytic performance, high catalytic activity, good selectivity and good stability, and shows good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1This is the UV Raman spectrum of the fully crystalline MWW structured titanium silicon molecular sieve catalyst prepared in [Example 1];
[0049] Figure 2 This is the X-ray diffraction pattern of the fully crystalline MWW structure titanium silicon molecular sieve catalyst prepared in [Example 1];
[0050] Figure 3 This is a scanning electron microscope image of the fully crystalline MWW structure titanium silicon molecular sieve catalyst prepared in [Example 1];
[0051] Figure 4 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 1];
[0052] Figure 5 This is the X-ray diffraction pattern of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 1];
[0053] Figure 6 This is a scanning electron microscope image of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 1];
[0054] Figure 7 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 2];
[0055] Figure 8 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 3];
[0056] Fig. 9 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 4];
[0057] Fig.10 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 5];
[0058] Fig.11 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 6];
[0059] Fig.12 This is the UV Raman spectrum of the MWW structured titanium silicon molecular sieve catalyst prepared in [Comparative Example 7]. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below in conjunction with embodiments, but is not limited to the following embodiments.
[0061] In the present invention, unless otherwise expressly stated, percentages and percentage contents are all measured by mass. Unless otherwise expressly stated, throughout the specification and claims, the term "comprise" or its variations such as "comprises" or "comprising" etc. shall be understood to include the stated steps or components, without excluding other steps or other components.
[0062] In the present invention, including in the following embodiments and comparative examples, the titanium species state, structure and morphology of the molecular sieve catalyst are determined by ultraviolet Raman spectroscopy, X-ray diffraction and scanning electron microscopy. The silicon-titanium molar ratio, boron-silicon molar ratio and aluminum-silicon molar ratio of the molecular sieve catalyst are determined by inductively coupled atomic emission spectroscopy. The micropore volume and mechanical strength of the molecular sieve catalyst are determined by nitrogen adsorption and desorption test and strength tester respectively.
[0063] In the present invention, the ultraviolet Raman spectrum test method is: using a domestic UV Raman-100 ultraviolet Raman spectrometer for testing, the excitation wavelength is 244nm, the laser power irradiated on the sample is 5.0mW, and the spectral resolution is 4cm -1 .
[0064] In the present invention, the X-ray diffraction test method is: using Japan Rigaku Ultima IV X-ray powder diffractometer to analyze the physical phase of the sample, Cu Kα line is used as the radiation source Nickel filter, 2θ scanning range 2-50°, operating voltage 40 kV, current 40 mA, scanning rate 10° / min.
[0065] In the present invention, the scanning electron microscope test method is: using a Hitachi S-4800 electron microscope for testing, with an acceleration voltage of 3 kV.
[0066] In the present invention, the inductively coupled atomic emission spectrometry testing method is: using a Varian-2000 analyzer to analyze the silicon-titanium molar ratio, boron-silicon molar ratio, and aluminum-silicon molar ratio in the sample, and dissolving the sample in a hydrofluoric acid solution before the test.
[0067] In the present invention, the nitrogen adsorption-desorption test method is: using the American Micromeritics ASAP2460 instrument to measure the nitrogen adsorption-desorption isotherm of the sample, and the micropore volume is obtained based on the measurement temperature of 77K. Before the test, the sample is vacuum pretreated at 573K for 6 hours.
[0068] In the present invention, the mechanical strength test method is: use DL-2 particle strength tester to test, first test the size of the catalyst in the force direction, then measure the external force required to extrude the catalyst into powder, and divide the external force by the size to obtain the mechanical strength of the catalyst.
[0069] In the present invention, the reaction liquid after passing through the catalyst bed is collected, the concentration of hydrogen peroxide in the reaction liquid is determined by cerium sulfate titration method, and the residual hydrogen peroxide rate and the hydrogen peroxide conversion rate are calculated.
[0070]
[0071] Hydrogen peroxide conversion rate % = 1-hydrogen peroxide residual rate %.
[0072] In the present invention, gas chromatography is used to analyze the product composition, and the selectivity of the main product epoxide and the by-product diol and alcohol ether, and the main-by-product ratio are calculated.
[0073]
[0074]
[0075] In the present invention, the timing starts from when the two plunger pumps are turned on, and ends when the residual rate of hydrogen peroxide in the reaction solution reaches 2%. The corresponding operating time is the catalyst stabilization time.
[0076] [Example 1]
[0077] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0078] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0079] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0080] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S1.
[0081] The UV Raman spectrum of the catalyst S1 is as follows Figure 1 As shown, 343, 485, 529, and 1094 cm -1 Spectral peak. Among them, 343cm -1 The peaks are attributed to the MWW structure, 485, 529, 1094 cm -1 The peaks are attributed to framework tetracoordinated titanium species, and their appearance indicates that the state of the titanium species is good.
[0082] The X-ray diffraction pattern of the catalyst S1 is as follows Figure 2 As shown, strong diffraction peaks appear at 2θ of 7.2°, 8.0°, 10.0°, 14.3°, 22.8°, and 26.1°, indicating that S1 has an MWW structure and high crystallinity.
[0083] The SEM image of the catalyst S1 is as follows Figure 3 As shown, the sample exhibits a lamellar morphology and no nanoparticles are observed, indicating that S1 is a pure phase single MWW structure.
[0084] The catalyst S1 has a silicon-titanium molar ratio of 50 and a boron-silicon molar ratio of 0.010.
[0085] The micropore volume of the catalyst S1 is 0.18 cm 3 / g, and the mechanical strength is 70N / cm.
[0086] [Example 2]
[0087] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 5, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 0.9 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0088] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0089] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0090] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S2.
[0091] The UV Raman spectrum of the catalyst S2 is Figure 1 Similarly, 341, 487, 527, and 1096 cm -1 Compared with S1, S2 has a peak of 1096cm -1 The peak at 341cm -1 The intensity ratio of the spectral peaks is much larger, indicating that the framework of S2 contains much more tetracoordinated titanium species than that of S1.
[0092] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S2 are respectively Figure 2 , Figure 3 similar.
[0093] The catalyst S2 has a silicon-titanium molar ratio of 10 and a boron-silicon molar ratio of 0.004.
[0094] The micropore volume of the catalyst S2 is 0.15 cm 3 / g, and the mechanical strength is 46N / cm.
[0095] [Example 3]
[0096] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 200, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 9 g of cellulose and 45 g of potassium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0097] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0098] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0099] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S3.
[0100] The UV Raman spectrum of the catalyst S3 is Figure 1 Similarly, 345, 482, 530, and 1092 cm -1 Compared with S1, S3 has a peak of 1092cm -1 The peak at 345cm -1 The intensity ratio of the spectral peak is much smaller, indicating that the framework tetracoordinated titanium species of S3 is much less than that of S1.
[0101] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S3 are respectively Figure 2 , Figure 3 similar.
[0102] The catalyst S3 has a silicon-titanium molar ratio of 500 and a boron-silicon molar ratio of 0.019.
[0103] The micropore volume of the catalyst S3 is 0.20 cm 3 / g, and the mechanical strength is 100N / cm.
[0104] [Example 4]
[0105] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 9 g of an amorphous binder (the amorphous binder includes 6 g of silica sol with a silicon dioxide mass fraction of 25%, 3 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 90 g of water is added, stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, it is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0106] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0107] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0108] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S4.
[0109] The UV Raman spectrum of the catalyst S4 is Figure 1 Similarly, 342, 486, 527, and 1095 cm -1 Spectrum Peak.
[0110] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S4 are respectively Figure 2 , Figure 3 similar.
[0111] The catalyst S4 has a silicon-titanium molar ratio of 40 and a boron-silicon molar ratio of 0.005.
[0112] The micropore volume of the catalyst S4 is 0.12 cm 3 / g, and the mechanical strength is 30N / cm.
[0113] [Example 5]
[0114] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 135 g of an amorphous binder (the amorphous binder includes 130 g of a silica sol with a silicon dioxide mass fraction of 20% and 5 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 30 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0115] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0116] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0117] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S5.
[0118] The UV Raman spectrum of the catalyst S5 is Figure 1 Similarly, 343, 486, 527, and 1098 cm -1 Spectrum Peak.
[0119] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S5 are respectively Figure 2 , Figure 3 similar.
[0120] The catalyst S5 has a silicon-titanium molar ratio of 66 and a boron-silicon molar ratio of 0.003.
[0121] The micropore volume of the catalyst S5 is 0.19 cm 3 / g, and the mechanical strength is 88N / cm.
[0122] [Example 6]
[0123] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of silica sol with a silicon dioxide mass fraction of 40% and 20 g of aluminum hydroxide), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, it is dried at 100° C. for 8 hours and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0124] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0125] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0126] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S6.
[0127] The UV Raman spectrum of the catalyst S6 is Figure 1 Similarly, 349, 479, 535, and 1088 cm -1 Compared with S1, the peaks of the tetracoordinated titanium species in S6 are located at 491, 523, and 1088 cm -1 This indicates that the titanium species state of S6 is not as good as that of S1.
[0128] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S6 are respectively Figure 2 , Figure 3 similar.
[0129] The catalyst S6 has a silicon-titanium molar ratio of 48 and an aluminum-silicon molar ratio of 0.012.
[0130] The micropore volume of the catalyst S6 is 0.18 cm 3 / g, and the mechanical strength is 82N / cm.
[0131] [Example 7]
[0132] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of silica sol with a silica mass fraction of 40%, 10 g of boric acid, and 10 g of aluminum hydroxide), 3 g of sesbania powder, and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0133] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0134] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0135] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S7.
[0136] The UV Raman spectrum of the catalyst S7 is Figure 1 Similarly, 346, 482, 533, and 1092 cm -1 Compared with S1, the peaks of the tetracoordinated titanium species in S7 are located at 482, 533, and 1092 cm -1 This indicates that the titanium species state of S7 is not as good as that of S1.
[0137] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S7 are respectively Figure 2 , Figure 3 similar.
[0138] The catalyst S7 has a silicon-titanium molar ratio of 48, a boron-silicon molar ratio of 0.006, and an aluminum-silicon molar ratio of 0.008.
[0139] The micropore volume of the catalyst S7 is 0.18 cm 3 / g, and the mechanical strength is 75N / cm.
[0140] [Example 8]
[0141] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder comprises 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a four-leaf clover-shaped molding.
[0142] (2) 90 g of the four-leaf clover-shaped product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a four-leaf clover-shaped catalyst precursor was obtained.
[0143] (3) 60 g of the four-leaf clover-shaped catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a four-leaf clover-shaped sample after the first solution treatment.
[0144] 40 g of the four-leaf clover-shaped sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed and dried at 100°C for 8 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S8.
[0145] The UV Raman spectrum of the catalyst S8 is Figure 1 Similarly, 343, 485, 529, and 1094 cm -1 Spectrum Peak.
[0146] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S8 are respectively Figure 2 , Figure 3 similar.
[0147] The catalyst S8 has a silicon-titanium molar ratio of 49 and a boron-silicon molar ratio of 106.
[0148] The micropore volume of the catalyst S8 is 0.16 cm 3 / g, and the mechanical strength is 78N / cm.
[0149] [Example 9]
[0150] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After spheronization and granulation, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a spherical molded product.
[0151] (2) 90 g of the spherical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. The product was washed and dried at 100° C. for 8 hours to obtain a spherical catalyst precursor.
[0152] (3) 60 g of the spherical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a spherical sample after the first solution treatment.
[0153] 40 g of the spherical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed and dried at 100°C for 8 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S9.
[0154] The UV Raman spectrum of the catalyst S9 is Figure 1 Similarly, 343, 485, 529, and 1094 cm -1 Spectrum Peak.
[0155] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S9 are respectively Figure 2 , Figure 3 similar.
[0156] The catalyst S9 has a silicon-titanium molar ratio of 51 and a boron-silicon molar ratio of 0.011.
[0157] The micropore volume of the catalyst S9 is 0.15 cm 3 / g, and the mechanical strength is 56N / cm.
[0158] [Example 10]
[0159] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0160] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 600 g of a 0.3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0161] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0162] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S10.
[0163] The UV Raman spectrum of the catalyst S10 is Figure 1 Similarly, 343, 483, 529, and 1096 cm-1 Spectrum Peak.
[0164] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S10 are respectively Figure 2 , Figure 3 similar.
[0165] The catalyst S10 has a silicon-titanium molar ratio of 47 and a boron-silicon molar ratio of 0.007.
[0166] The micropore volume of the catalyst S10 is 0.14 cm 3 / g, and the mechanical strength is 52N / cm.
[0167] [Example 11]
[0168] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0169] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 9 g of a 15 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0170] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0171] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S11.
[0172] The UV Raman spectrum of the catalyst S11 is Figure 1 Similarly, 344, 485, 530, and 1093 cm -1 Spectrum Peak.
[0173] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S11 are respectively Figure 2 , Figure 3 similar.
[0174] The catalyst S11 has a silicon-titanium molar ratio of 52 and a boron-silicon molar ratio of 0.011.
[0175] The micropore volume of the catalyst S11 is 0.16 cm 3 / g, and the mechanical strength is 78N / cm.
[0176] [Example 12]
[0177] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0178] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 9 g of a 15 mol / L piperidine solution without contacting each other, and crystallized at 130° C. for 9 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0179] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0180] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S12.
[0181] The UV Raman spectrum of the catalyst S12 is Figure 1 Similarly, 343, 486, 529, and 1095 cm -1 Spectrum Peak.
[0182] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S12 are respectively Figure 2 , Figure 3 similar.
[0183] The silicon-titanium molar ratio of the catalyst S12 is 49, and the boron-silicon molar ratio is 0.010.
[0184] The micropore volume of the catalyst S12 is 0.10 cm 3 / g, and the mechanical strength is 45N / cm.
[0185] [Example 13]
[0186] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0187] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 9 g of a 15 mol / L piperidine solution without contacting each other, and crystallized at 190° C. for 1 day in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0188] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0189] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S13.
[0190] The UV Raman spectrum of the catalyst S13 is Figure 1 Similarly, 345, 485, 532, and 1092 cm -1 Spectrum Peak.
[0191] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S13 are respectively Figure 2 , Figure 3 similar.
[0192] The catalyst S13 has a silicon-titanium molar ratio of 54 and a boron-silicon molar ratio of 0.013.
[0193] The micropore volume of the catalyst S13 is 0.15 cm 3 / g, and the mechanical strength is 75N / cm.
[0194] [Example 14]
[0195] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0196] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L hexamethyleneimine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0197] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0198] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed and dried at 100°C for 8 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S14.
[0199] The UV Raman spectrum of the catalyst S14 is Figure 1 Similarly, 344, 485, 529, and 1093 cm -1 Spectrum Peak.
[0200] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S14 are respectively Figure 2 , Figure 3 similar.
[0201] The catalyst S14 has a silicon-titanium molar ratio of 50 and a boron-silicon molar ratio of 0.010.
[0202] The micropore volume of the catalyst S14 is 0.19 cm 3 / g, and the mechanical strength is 80N / cm.
[0203] [Example 15]
[0204] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0205] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0206] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 12 mol / L nitric acid solution at a solid-liquid mass ratio of 1:80, treated at 130° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0207] 40 grams of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:20, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S15.
[0208] The UV Raman spectrum of the catalyst S15 is Figure 1 Similarly, 337, 491, 523, and 1100 cm -1 Spectrum Peak.
[0209] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S15 are respectively Figure 2 , Figure 3 similar.
[0210] The catalyst S15 has a silicon-titanium molar ratio of 96 and a boron-silicon molar ratio of 0.001.
[0211] The micropore volume of the catalyst S15 is 0.17 cm 3 / g, and the mechanical strength is 58N / cm.
[0212] [Example 16]
[0213] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0214] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0215] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 0.2 mol / L hydrochloric acid solution at a solid-liquid mass ratio of 1:80, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0216] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.01 mol / L acetic acid solution at a solid-liquid mass ratio of 1:80, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, denoted as S16.
[0217] The UV Raman spectrum of the catalyst S16 is Figure 1 Similarly, 344, 484, 531, and 1091 cm -1 Spectrum Peak.
[0218] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S16 are respectively Figure 2 , Figure 3 similar.
[0219] The catalyst S16 has a silicon-titanium molar ratio of 34 and a boron-silicon molar ratio of 0.04.
[0220] The micropore volume of the catalyst S16 is 0.16 cm 3 / g, and the mechanical strength is 72N / cm.
[0221] [Example 17]
[0222] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0223] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0224] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, reacted at 120° C. for 8 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0225] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.01 mol / L potassium chloride solution at a solid-liquid mass ratio of 1:50, reacted at 100°C for 8 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S17.
[0226] The UV Raman spectrum of the catalyst S17 is Figure 1 Similarly, 340, 488, 524, and 1098 cm -1 Spectrum Peak.
[0227] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S17 are respectively Figure 2 , Figure 3 similar.
[0228] The silicon-titanium molar ratio of the catalyst S17 is 63, and the boron-silicon molar ratio is 0.006.
[0229] The micropore volume of the catalyst S17 is 0.14 cm 3 / g, and the mechanical strength is 52N / cm.
[0230] [Example 18]
[0231] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0232] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0233] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, reacted at 60° C. for 36 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0234] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.1 mol / L sodium sulfate solution at a solid-liquid mass ratio of 1:50, reacted at 20°C for 48 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain a fully crystalline MWW structured titanium silicon molecular sieve catalyst, recorded as S18.
[0235] The UV Raman spectrum of the catalyst S18 is Figure 1 Similarly, 346, 483, 534, and 1092 cm -1 Spectrum Peak.
[0236] The X-ray diffraction pattern and scanning electron microscope image of the catalyst S18 are respectively Figure 2 , Figure 3 similar.
[0237] The silicon-titanium molar ratio of the catalyst S18 is 44, and the boron-silicon molar ratio is 0.012.
[0238] The micropore volume of the catalyst S18 is 0.15 cm 3 / g, and the mechanical strength is 75N / cm.
[0239] [Examples 19 to 25]
[0240] The fully crystalline MWW structure titanium silicon molecular sieve catalyst prepared in the above embodiment is subjected to liquid phase continuous propylene epoxidation reaction in a stainless steel fixed bed reaction device, 2 grams of fully crystalline MWW structure titanium silicon molecular sieve catalyst is crushed into 20-40 mesh particles and filled in a stainless steel reaction tube, and both ends of the reaction tube are filled with glass beads. The reaction is controlled under the conditions of liquid phase epoxidation, the reaction temperature is 40°C, the reaction pressure is 2.0MPa, and the mode of lower feeding and upper discharging is adopted. Nitrogen is used to balance the propylene pressure to 2.5MPa to ensure that the propylene is completely liquefied, and the propylene raw material liquid is fed separately, which is recorded as raw material liquid A; an aqueous solution with a mass fraction of hydrogen peroxide of 30% is selected to prepare an aqueous hydrogen peroxide solution containing a concentration of 15ppm of diammonium phosphate, which is mixed with the solvent acetonitrile, which is recorded as raw material liquid B. The two raw material liquids were fed separately by plunger pumps. The two raw material liquids were premixed before flowing through the catalyst bed. In the total raw material feed flow, the mass fraction of propylene was 18.7%, the mass fraction of acetonitrile was 61.0%, the molar ratio of propylene to hydrogen peroxide was 1:0.4, and the flow rate of the total raw material per unit mass of catalyst was 6 mL·g cat. -1 ·h -1 The reaction liquid after passing through the catalyst bed was collected, and the results are shown in Table 1.
[0241] Table 1 Performance of catalysts for propylene epoxidation in Examples 1, 6, 7, 11, 16, 17, and 18
[0242]
[0243]
[0244] Note: a. The conversion rate and residual rate of hydrogen peroxide are the data at the beginning of the reaction;
[0245] b. During continuous reaction, the selectivity of propylene oxide and the ratio of main products to by-products remain stable;
[0246] c. Catalyst stabilization time refers to the operation time from the beginning of the reaction to the time when the hydrogen peroxide conversion rate is less than 98.0% and the residual rate of hydrogen peroxide in the reaction solution reaches 2%.
[0247] [Examples 26 to 32]
[0248] The fully crystalline MWW structure titanium silicon molecular sieve catalyst prepared in the above embodiment is used for the liquid phase continuous epoxidation reaction of 1-pentene in a stainless steel fixed bed reaction device. 2 grams of fully crystalline MWW structure titanium silicon molecular sieve catalyst is crushed into 20-40 mesh particles and filled in a stainless steel reaction tube. Both ends of the reaction tube are filled with glass beads. The reaction is controlled under the conditions of liquid phase epoxidation, the reaction temperature is 60°C, the reaction pressure is 0.6MPa, and the mode of lower feeding and upper discharging is adopted. The 1-pentene raw material liquid is fed separately, which is recorded as raw material liquid A; an aqueous solution with a mass fraction of hydrogen peroxide of 30% is selected to prepare an aqueous hydrogen peroxide solution containing a potassium carbonate concentration of 15ppm, which is mixed with the solvent acetonitrile and recorded as raw material liquid B. The two raw material liquids were fed separately by plunger pumps. The two raw material liquids were premixed before flowing through the catalyst bed. In the total raw material feed flow, the mass fraction of 1-pentene was 27.7%, the mass fraction of acetonitrile was 54.2%, the molar ratio of 1-pentene to hydrogen peroxide was 1:0.4, and the flow rate of the total raw material per unit mass of catalyst was 4 mL·g cat. -1 ·h -1 The reaction liquid after passing through the catalyst bed was collected, and the results are shown in Table 2 below:
[0249] Table 2 Performance of catalysts for 1-pentene epoxidation in Examples 1, 6, 7, 11, 16, 17, and 18
[0250]
[0251]
[0252] Note: a. The conversion rate and residual rate of hydrogen peroxide are the data at the beginning of the reaction;
[0253] b. During continuous reaction, the selectivity of 1,2-epoxypentane and the ratio of main products to by-products remain stable;
[0254] c. Catalyst stabilization time refers to the operation time from the beginning of the reaction to the time when the hydrogen peroxide conversion rate is less than 98.0% and the residual rate of hydrogen peroxide in the reaction solution reaches 2%.
[0255] [Comparative Example 1]
[0256] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silica mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours and then calcined at 550° C. for 6 hours to obtain an MWW structured titanium silicon molecular sieve catalyst, which is recorded as D1.
[0257] The UV Raman spectrum of D1 is shown in Figure 4 As shown, only 487 and 1103 cm -1 spectral peaks, indicating that the titanium species is in poor condition.
[0258] The X-ray diffraction pattern of D1 is shown in Figure 5 As shown in the figure, diffraction peaks appear at 2θ of 7.2°, 8.0°, 10.0°, 14.3°, 22.8°, and 26.1°, indicating that the main body of D1 is an MWW structure, but there is a strong broad diffraction peak in the 17.5-30° region, indicating that D1 has an amorphous species. Figure 6 As shown, in addition to the lamellar morphology, small nanoparticles were also observed, which again indicated that D1 existed in an amorphous form.
[0259] The silicon-titanium molar ratio of D1 is 38, and the boron-silicon molar ratio is 0.167.
[0260] The micropore volume of D1 is 0.06 cm 3 / g, and the mechanical strength is 27N / cm.
[0261] [Comparative Example 2]
[0262] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0263] (2) 60 g of the cylindrical molded product of step (1) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0264] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain an MWW structured titanium silicon molecular sieve catalyst, recorded as D2.
[0265] The UV Raman spectrum of D2 is as follows Figure 7 As shown, the observed -1 spectral peaks, indicating that the titanium species is in poor condition.
[0266] The X-ray diffraction pattern and scanning electron microscope image of D2 are respectively Figure 5 , Figure 6 similar.
[0267] The silicon-titanium molar ratio of D2 is 52, and the boron-silicon molar ratio is 0.005.
[0268] The micropore volume of D2 is 0.08 cm 3 / g, and the mechanical strength is 16N / cm.
[0269] [Comparative Example 3]
[0270] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0271] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. The product was washed and dried at 100° C. for 8 hours to obtain a MWW structured titanium silicon molecular sieve catalyst, which was recorded as D3.
[0272] The UV Raman spectrum of D3 is as follows Figure 8 As shown, 484, 560, 704, and 1092 cm -1 spectral peaks, indicating that the titanium species is in poor condition.
[0273] The silicon-titanium molar ratio of D3 is 36, and the boron-silicon molar ratio is 0.091.
[0274] The micropore volume of D3 is 0.04 cm 3 / g, and the mechanical strength is 82N / cm.
[0275] [Comparative Example 4]
[0276] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0277] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0278] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain an MWW structure titanium silicon molecular sieve catalyst, recorded as D4.
[0279] The UV Raman spectrum of D4 is as follows Fig. 9 As shown, 343, 490, 568, and 1096 cm -1 spectral peak, indicating that its titanium species state is not as good as that of S1 in Example 1.
[0280] The silicon-titanium molar ratio of D4 is 49, and the boron-silicon molar ratio is 0.012.
[0281] The micropore volume of D4 is 0.16 cm 3 / g, and the mechanical strength is 74N / cm.
[0282] [Comparative Example 5]
[0283] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silicon dioxide mass fraction of 40% and 20 g of boric acid), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0284] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0285] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0286] 40 g of the cylindrical sample after the first solution treatment was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain an MWW structured titanium silicon molecular sieve catalyst, recorded as D5.
[0287] The UV Raman spectrum of D5 is shown in Fig.10 As shown, 342, 487, 572, and 1102 cm -1 spectral peak, indicating that its titanium species state is not as good as that of S1 in Example 1.
[0288] The silicon-titanium molar ratio of D5 is 68, and the boron-silicon molar ratio is 0.003.
[0289] The micropore volume of D5 is 0.18 cm 3 / g, and the mechanical strength is 58N / cm.
[0290] [Comparative Example 6]
[0291] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 95 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silica mass fraction of 40% and 20 g of boric acid) and 3 g of sesbania powder are mixed uniformly under mechanical stirring conditions, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0292] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0293] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0294] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain an MWW structured titanium silicon molecular sieve catalyst, recorded as D6.
[0295] The UV Raman spectrum of D6 is shown in Fig.11 As shown, 344, 487, 565, and 1102 cm-1 spectral peak, indicating that its titanium species state is not as good as that of S1 in Example 1.
[0296] The X-ray diffraction pattern and scanning electron microscope image of D6 are respectively Figure 5 , Figure 6 similar.
[0297] The silicon-titanium molar ratio of D6 is 53, and the boron-silicon molar ratio is 0.011.
[0298] The micropore volume of D6 is 0.09 cm 3 / g, and the mechanical strength is 46N / cm.
[0299] [Comparative Example 7]
[0300] (1) 90 g of MWW structured titanium silicon molecular sieve powder with a silicon-titanium molar ratio of 30, 75 g of an amorphous binder (the amorphous binder includes 75 g of a silica sol with a silica mass fraction of 40%), 3 g of sesbania powder and 8.4 g of sodium fluoride are mixed uniformly under mechanical stirring conditions, and then 80 g of water is added, and the mixture is stirred and kneaded for 4 hours to obtain a solid mixture with a certain viscosity. After mechanical extrusion molding, the mixture is dried at 100° C. for 8 hours, and then calcined at 550° C. for 6 hours to obtain a cylindrical molded product.
[0301] (2) 90 g of the cylindrical molded product of step (1) was placed on top of 60 g of a 3 mol / L piperidine solution without contacting each other, and crystallized at 170° C. for 2 days in a closed environment. After washing and drying at 100° C. for 8 hours, a cylindrical catalyst precursor was obtained.
[0302] (3) 60 g of the cylindrical catalyst precursor described in step (2) was mixed with 2 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80° C. for 24 hours, washed, dried at 100° C. for 8 hours and calcined at 550° C. for 6 hours to obtain a cylindrical sample after the first solution treatment.
[0303] 40 g of the cylindrical sample after the first solution treatment was mixed with 0.0008 mol / L nitric acid solution at a solid-liquid mass ratio of 1:50, treated at 80°C for 24 hours, washed, dried at 100°C for 8 hours and calcined at 550°C for 6 hours to obtain an MWW structured titanium silicon molecular sieve catalyst, recorded as D7.
[0304] The UV Raman spectrum of D7 is shown in Fig.12 As shown, 491, 562, and 1092 cm -1 spectral peaks, indicating that the titanium species is in poor condition.
[0305] The X-ray diffraction pattern and scanning electron microscope image of D7 are respectively Figure 5 , Figure 6 similar.
[0306] The silicon-titanium molar ratio of D7 is 36.
[0307] The micropore volume of D7 is 0.08 cm 3 / g, and the mechanical strength is 23N / cm.
[0308] [Comparative Examples 8 to 14]
[0309] The MWW structured titanium silicon molecular sieve catalysts D1 to D6 obtained in Comparative Examples 1 to 6 were subjected to liquid phase continuous epoxidation of propylene according to the reaction conditions of Examples 19 to 25. The reaction results are shown in Table 3 below:
[0310] Table 3 Comparative Examples 1 to 7 Catalyst D1 to D7 Catalytic Propylene Epoxidation Performance
[0311]
[0312] Note: a. The conversion rate and residual rate of hydrogen peroxide are the data at the beginning of the reaction;
[0313] b. During continuous reaction, the selectivity of propylene oxide and the ratio of main products to by-products remain stable;
[0314] c. Catalyst stabilization time refers to the operation time from the beginning of the reaction to the time when the hydrogen peroxide conversion rate is less than 98.0% and the residual rate of hydrogen peroxide in the reaction solution reaches 2%.
[0315] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A fully crystalline MWW structure titanium silicon molecular sieve catalyst, wherein the ultraviolet Raman spectrum of the molecular sieve catalyst is 343±6cm -1 、485±6cm -1 、529±6cm -1 and 1094±6cm -1 A peak appears at The molar ratio of silicon to titanium in the molecular sieve catalyst is 5 to 500; the molecular sieve catalyst also includes at least one element of boron and aluminum; the molar ratio of boron to silicon is 0 to 0.10; the molar ratio of aluminum to silicon is 0 to 0.10; The micropore volume of the molecular sieve catalyst is 0.10 to 0.20 cm 3 / g; The mechanical strength of the molecular sieve catalyst is 30 to 100 N / cm.
2. The molecular sieve catalyst according to claim 1, characterized in that: The molar ratio of silicon to titanium in the molecular sieve catalyst is 10 to 200; the molar ratio of boron to silicon in the molecular sieve catalyst is 0 to 0.040; and the molar ratio of aluminum to silicon in the molecular sieve catalyst is 0 to 0.
04.
3. The molecular sieve catalyst according to claim 2, characterized in that: The molecular sieve catalyst includes boron element; in the molecular sieve catalyst, the molar ratio of boron to silicon is 0.001 to 0.
040.
4. The molecular sieve catalyst according to claim 1, characterized in that: The micropore volume of the molecular sieve catalyst is 0.12 to 0.18 cm 3 / g.
5. The molecular sieve catalyst according to claim 1, characterized in that: The mechanical strength of the molecular sieve catalyst is 40 to 90 N / cm.
6. A method for preparing a fully crystalline MWW structure titanium silicon molecular sieve catalyst, comprising the following steps: (1) kneading MWW structure titanium silicon molecular sieve powder, a binder, a pore-forming agent, and a fluoride into a mold, and first calcining to obtain a molded product; (2) crystallizing the product obtained in step (1) in an environment containing an organic amine solution to obtain a catalyst precursor; (3) treating the catalyst precursor of step (2) with solution A, performing a second calcination, and then treating with solution B to obtain the molecular sieve catalyst; The binder in step (1) comprises a silicon source and at least one selected from a boron source and an aluminum source; in the composition of the binder, in terms of oxides, the molar ratio of SiO2:B2O3:Al2O3=1:x:y, wherein x=0-1, y=0-1, and x+y=0.01-2; The process of crystallization in an environment containing an organic amine solution in step (2) comprises: step (1) placing the molded object on the organic amine solution for crystallization, and the molded object is not in contact with the organic amine solution; The crystallization conditions in step (2) are: a crystallization temperature of 130 to 190° C. and a crystallization time of 1 to 9 days; The solute A in the A solution is at least one selected from nitric acid and hydrogen chloride; the concentration of the A solution is 0.2-12 mol / L; the solid-liquid mass ratio of the catalyst precursor to the A solution in the A solution treatment is 1:10-80; the temperature of the A solution treatment is 60-130°C, and the time is 1-48 hours; The solute B in the B solution is at least one selected from nitric acid, acetic acid, potassium chloride, and sodium sulfate; the concentration of the B solution is 0.0001-0.1 mol / L; the solid-liquid mass ratio of the catalyst precursor to the B solution in the B solution treatment is 1:10-80; the temperature of the B solution treatment is 20-100°C, and the time is 1-48 hours.
7. The preparation method according to claim 6, characterized in that: The silicon source is selected from at least one of silica sol, water glass, silicon powder and tetraethyl orthosilicate; the boron source is selected from at least one of boric acid, boron trioxide and borate; the aluminum source is selected from at least one of aluminum trioxide, aluminum hydroxide, sodium aluminate, aluminum nitrate and aluminum sulfate.
8. The preparation method according to any one of claims 6-7, characterized in that: The pore-forming agent in step (1) is selected from at least one of sesbania powder, cellulose, chitosan, lignin, starch, polyethylene glycol, triblock copolymers P123 and F127; the fluoride in step (1) is selected from at least one of sodium fluoride, potassium fluoride and ammonium fluoride; the mass ratio of the raw materials, MWW structure titanium silicon molecular sieve powder, binder, pore-forming agent and fluoride in step (1) is 1:0.1-1.5:0.005-0.1:0.01-0.
5.
9. The preparation method according to claim 6, characterized in that: The organic amine is at least one selected from piperidine and hexamethyleneimine; the concentration of the organic amine solution is 0.2-20 mol / L; the mass ratio of the molded object to the organic amine solution is 0.1-10:
1.
10. The preparation method according to claim 6, characterized in that: The first calcination condition in step (1) is calcination in an oxygen-containing atmosphere at 450-650° C. for 4-12 hours; the second calcination condition in step (3) is calcination in an oxygen-containing atmosphere at 450-650° C. for 4-12 hours.
11. The molecular sieve catalyst prepared by the preparation method according to any one of claims 6 to 10.
12. Use of the molecular sieve catalyst according to any one of claims 1 to 5 or the molecular sieve catalyst according to claim 11 in olefin epoxidation reaction.
Citation Information
Patent Citations
A propylene epoxidation catalyst, its preparation method and application
CN103464197B
Propylene epoxidation catalyst
CN1268400A
Process for preparing composite catalyst and its application
CN1346705A
Preparation of porous crystalline synthetic material comprised of silicon and titanium oxides
US4410501A
Fluorine-containing titanium-silicon molecular sieve with MWW (Manual Wire Wrap) structure and preparation method and application thereof
CN102627291A